Pazopanib and HDAC inhibitors interact to kill sarcoma cells - Tavallai, Seyedmehrad (Landes Bioscience, 2014)
The present studies were to determine whether the multi-kinase inhibitor pazopanib interacted with histone deacetylase inhibitors (HDACI: valproate, vorinostat) to kill sarcoma cells. In multiple sarcoma cell lines, at clinically achievable doses, pazopanib and HDACI interacted in an additive to greater than additive fashion to cause tumor cell death. The drug combination increased the numbers of LC3-GFP and LC3-RFP vesicles. Knockdown of Beclin1 or ATG5 significantly suppressed drug combination lethality. Expression of c-FLIP-s, and to a lesser extent BCL-XL or dominant negative caspase 9 reduced drug combination toxicity; knock down of FADD or CD95 was protective. Expression of both activated AKT and activated MEK1 was required to strongly suppress drug combination lethality. The drug combination inactivated mTOR and expression of activated mTOR strongly suppressed drug combination lethality. Treatment of animals carrying sarcoma tumors with pazopanib and valproate resulted in a greater than additive reduction in tumor volume compared with either drug individually. As both pazopanib and HDACIs are FDA-approved agents, our data argue for further determination as to whether this drug combination is a useful sarcoma therapy in the clinic.